2022
DOI: 10.3847/1538-4357/ac6fd4
|View full text |Cite
|
Sign up to set email alerts
|

Hard X-Ray Emission in Centaurus A

Abstract: We use 13 yr of Swift/BAT observations to probe the nature and origin of the hard X-ray (14–195 KeV) emission in Centaurus A. Since the beginning of the Swift operation in 2004, significant X-ray variability in the 14–195 KeV band has been detected, with mild changes in the source spectrum. Spectral variations became more eminent after 2013, following a softer-when-brighter trend. Using the power spectral density (PSD) method, we find that the observed hard X-ray photon flux variations are consistent with a re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…2581-2590) showed relatively soft spectra with photon indices of roughly 2.1 (SPI) and 2.0 (ISGRI), though the errors are large. During this period, the source was at its lowest flux level observed by INTEGRAL, which does not confirm the behavior reported by Rani et al (2022).…”
Section: Spectral Variabilitycontrasting
confidence: 88%
See 3 more Smart Citations
“…2581-2590) showed relatively soft spectra with photon indices of roughly 2.1 (SPI) and 2.0 (ISGRI), though the errors are large. During this period, the source was at its lowest flux level observed by INTEGRAL, which does not confirm the behavior reported by Rani et al (2022).…”
Section: Spectral Variabilitycontrasting
confidence: 88%
“…In their work on Cen A, Rani et al (2022) also showed that the 230 GHz flux correlates with the hard X-ray flux with no time lag. (Israel et al 2008 found similar results.)…”
Section: Comparison With Previous Workmentioning
confidence: 96%
See 2 more Smart Citations
“…Many authors have reported that Cen A's spectrum does not change with flux [2,4,13,21,22]. In another side, Swift/BAT recently reported spectral softening after 2013 [17]. We searched for spectral variability in the INTEGRAL data by fitting the SPI 25 − 70 keV and ISGRI 34 − 68 keV spectra independently to a power-law model.…”
Section: Spectral Variabilitymentioning
confidence: 99%